Curettage and Policresulen Tampon as A Modality Treatment in Management of Verucca - Simamora, Huntal; Lestari, Puri Ambar; Bangun, Kristaninta; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Verruca, also known as warts is a skin disease characterized by epidermal growth. Verruca may occur anywhere especially on palms and soles. It appears as a rough, dark-grey colored surface and has similar features with clavus or callus, which frequently lead to inappropriate management.Patient and Method : We report two cases with verruca, one was on sole and another was on palm area treated with curettage and chemical ablation using policresulen solution. Both cases have histories of recurrences from the previous treatment, which was excision and primary closure.Results : The wound healed within seven days after treatment. There were no recurrences found after 6-month follow up.Summary : Our treatment (curettage and chemical ablation using policresulen) has two advantages: (1) it can avoid excessive tissue removal since this lesion only afect epidermal layer.